If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 12 = 2x + 282 Reorder the terms: 12 + 12x = 2x + 282 Reorder the terms: 12 + 12x = 282 + 2x Solving 12 + 12x = 282 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 12x + -2x = 282 + 2x + -2x Combine like terms: 12x + -2x = 10x 12 + 10x = 282 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 10x = 282 + 0 12 + 10x = 282 Add '-12' to each side of the equation. 12 + -12 + 10x = 282 + -12 Combine like terms: 12 + -12 = 0 0 + 10x = 282 + -12 10x = 282 + -12 Combine like terms: 282 + -12 = 270 10x = 270 Divide each side by '10'. x = 27 Simplifying x = 27
| 10x-200=3x-11 | | 10x-2=3x-11 | | 6x+31=9x-5 | | 4(4x)+2(x)=70 | | R/8=72 | | 10-x=x+8 | | 9(x+1)-4x=5-(x-3) | | 10x+3=6x-4 | | 4X-5X+8X-7=6X+6X+12 | | f(x)=24ln(x)-0.8x | | 2xy^2+4=2(3-x^2y)dy | | 3x-1+3x=12 | | y=24x+45 | | 2x+1+x+10+x-3=56 | | -3+2x-=3-4x | | 8x-4/2=10 | | tanx=-1.732 | | 1/14÷13/14 | | 9/10÷7/10 | | 2-(7/2y)-(39/4y^2)=0 | | -1x^2+23=0 | | 2x^4p^2-yzq-3z^2=0 | | 4n+25+3n+29=180 | | 24+x+x=90 | | (x+3)(x)=75 | | 3x+32+1=180 | | 6x-19+1=180 | | 3x^4-2x^3+2x^2-2x-1=0 | | 5x+15=57-2x | | 5+15=57-2x | | F(x)=15x-5x^2 | | F(x)=15x-5x |